A comparative study for efficacy and safety of low doses of clonidine for hemodynamic stability in patients undergoing laparoscopic cholecystectomy - Choudhary, Ruchi; Singh, Preeti; Gupta, Surabhi; Khosla, P. P.; Matreja, Prithpal S.; Singh, Upmanyu (International Journal of Basic & Clinical Pharmacology, 2019)
Background: This randomized prospective double-blind study was designed to evaluate the efficacy and side effects of low doses clonidine for perioperative haemodynamic stability and postoperative recovery. Methods: Patient’s with ASA grade I–II undergoing laparoscopic cholecystectomy were randomized into three groups of 30 patients each. All patients received either normal saline 10 ml (Group I) or 0.8 µg/kg (Group II) or 1 µg/kg (Group III) over duration of 180 seconds, 10 min prior to laryngoscopy and intubation. Anaesthesia was induced with 1% propofol (2 mg/kg) and maintained with nitrous oxide 60% in oxygen and isoflurane. The parameters assessed at various time intervals were heart rate, systolic blood pressure, diastolic blood pressure, mean arterial pressure and sedation score. Results: Both doses of clonidine proved to be effective in perioperative haemodynamic stability. Clonidine 0.8 mcg/kg was as effectve and safer to Clonidine 1 mcg/kg for attenuatíon of the hemodynamíc responses to laparoscopy. There were no significant differences in the parameters of recovery between groups. Conclusions: Significant hemodynamic derangements can occur during laproscopic cholecystectomy at intubation, pneumoperitoneum and extubation. These were effectively attenuated by premedication with 0.8 mcg/kg and 1 mcg/kg of intravenous clonidine. Dose of 1 mcg/kg though found to be effective but produced adverse effects in form of hypotension and bradycardia.